2017
DOI: 10.1038/s41467-017-02039-5
|View full text |Cite
|
Sign up to set email alerts
|

Thin single crystal perovskite solar cells to harvest below-bandgap light absorption

Abstract: The efficiency of perovskite solar cells has surged in the past few years, while the bandgaps of current perovskite materials for record efficiencies are much larger than the optimal value, which makes the efficiency far lower than the Shockley–Queisser efficiency limit. Here we show that utilizing the below-bandgap absorption of perovskite single crystals can narrow down their effective optical bandgap without changing the composition. Thin methylammonium lead triiodide single crystals with tuned thickness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
522
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(539 citation statements)
references
References 42 publications
17
522
0
Order By: Relevance
“…The highest efficiency we have obtained is 15.12% for the small-area devices with an additional mp-TiO 2 layer. The V oc (1059 mV) and FF (>70%) are comparable with the best-performed devices with similar structure as reported in the literature [22], while the relatively smaller J sc is ascribed to the thinner perovskite layer (about 200 nm) and incomplete light absorption in our experiment [35].…”
Section: Measurements and Characterizationsupporting
confidence: 90%
“…The highest efficiency we have obtained is 15.12% for the small-area devices with an additional mp-TiO 2 layer. The V oc (1059 mV) and FF (>70%) are comparable with the best-performed devices with similar structure as reported in the literature [22], while the relatively smaller J sc is ascribed to the thinner perovskite layer (about 200 nm) and incomplete light absorption in our experiment [35].…”
Section: Measurements and Characterizationsupporting
confidence: 90%
“…A high-quality thick perovskite film is desirable to achieve a high device yield and reproducibility in making large-area solar modules. Besides, thicker perovskite films can not only improve the light harvesting 13,14 , but also broaden light response region by utilizing the below-band absorption 15 . As such, it is advantageous to construct a high-quality thick perovskite film with enough carrier diffusion length in PSCs to endorse both higher efficiency and manufacturing viability.…”
Section: Introductionmentioning
confidence: 99%
“…Huang and co-workers [1b] used the solvent annealing method to realize PCE of 15.6% with film thickness of 630 nm. Recently, Huang and co-workers [14] grew a 10 µm thick single-crystal film in order to reduce the bulk defect inside perovskite layer, and got a efficiency of 16.1%. Sun and coworkers [2c] demonstrated that a solvent retarding process before annealing would increase the precursor concentration for the as-cast perovskite-precursor layer, leading to champion PCE of 16.83% with film thickness ≈800 nm.…”
Section: Introductionmentioning
confidence: 99%